A Two-Dimensional Cell Model of Phases Transport in a Fluidized Bed Column: Development and Validation - Andrey Mitrofanov (Journal of Heat and Mass Transfer Research)
Fluidized bed apparatuses are widely used in chemical engineering. Description of the hydrodynamic state of the apparatus is the starting point for predicting most technological operations in gas-solid flows. The object of this study is the gas and solids distributions in a fluidized bed column. The key aim of the study is to develop a simple yet informative mathematical model of the migration of gas and particulate solids in a fluidized bed column. The model is developed to solve the problem in a two-dimensional formulation. The phase migrations of the fluidized bed along the height of the column are described on the basis of the mathematical apparatus of the theory of Markov chains, and an explicit difference scheme is used for the mathematical model of particle transfer in the radial direction. A cell of small but finite size acts as a representative volume of the simulated system. The representative volume of such geometry is apparently used for modeling the motion of fluidized bed phases for the first time. At the same time, it is precisely this model structure that corresponds to the tradition of identifying the radial and axial coefficients of particle macrodiffusion. Parametric identification of the model is carried out on the basis of the empirical relationships known from the literature. The numerical experiments performed in the study showed the qualitative consistency of the proposed model. A comparison of calculations with the results of a natural experiment also confirmed the presence of predictive capabilities in the model. Thus, the proposed model can be considered as a reliable scientific basis for computer methods for calculating fluidized bed devices.